One modification of k-ε turbulent model of two-phase flows - Lien, Hoang Duc; Antonov, I. S.; Nam, Nguyen Thanh (Vietnam Journal of Mechanics, 1998)
A modification of k-ε turbulent model is described with application to the numerical investigation of two-phase turbulent jets. In difference of existed two-parameter models, new three-parameter modification have been suggested. In this case an additional equation for transportation of turbulent energy of admixture – kP is used together with equations of transportation of carrier-phase turbulent energy – kg and its dissipation - ε. Additional dissipation terms in the above mentioned equations are defined in connection with a new examination of the between-phases interaction forces determining jet flows.